(untitled) (Journal of Global Accounting, 2023)
The study ascertained the effect of earnings management on the corporate sustainability performance of listed non-financial firms in Nigeria. The specific objective was to determine the effect of discretionary accruals and real earnings management on dividend per share. The study adopted the ex-post facto research design. The population of the study was made up of ninety-five non-financial firms listed on the Nigerian Exchange Group (NGX). Secondary data were extracted from the financial statements of the seventy-four (74) non-financial firms listed on the Nigerian Exchange Group which were sampled from the population over a period of 10 years (2012 – 2021). The analysis of data was done using descriptive statistics, panel unit root test, panel least square regression, and granger causality test. The findings showed that: discretionary accruals have a significant but negative effect on dividend per share while real earnings management has a non-significant negative effect on the dividend per share of listed non-financial firms on Nigeria Exchange Group. In conclusion, the deliberate managerial actions, intended towards disguising the real value of a firm’s assets, transactions, or financial position, have negative consequences on shareholders. The study recommends that companies should exercise prudence and transparency in their accrual decisions by implementing stringent internal controls and adhering to consistent and conservative accounting policies which can help mitigate the potential adverse effects of discretionary accruals on dividend distribution